2017
DOI: 10.1007/s00125-017-4347-7
|View full text |Cite
|
Sign up to set email alerts
|

Why is it so difficult to measure glucagon-like peptide-1 in a mouse?

Abstract: In mice, the GLP-1 metabolite is eliminated within a few minutes owing to endoproteolytic cleavage by NEP 24.11. Therefore, accurate measurement of GLP-1 secretion in mice requires assays for NEP 24.11 metabolites. Conventional sandwich ELISAs are inadequate because of endoproteolytic cleavage of the dipeptidyl peptidase-4-generated metabolite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 47 publications
(72 reference statements)
0
38
0
Order By: Relevance
“…However, we have not measured the active isoform of GLP-1 in these study samples. Furthermore, recent work reveals differences in the GLP-1 isoform profile between humans and rodents ( Windeløv et al, 2017 ). However, consistent with active GLP-1 primarily being secreted in the postprandial state, previous studies in rodents and humans show that fasting plasma active GLP-1 levels do not change after bariatric surgery ( Cummings et al, 2010 ; Laferrère et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have not measured the active isoform of GLP-1 in these study samples. Furthermore, recent work reveals differences in the GLP-1 isoform profile between humans and rodents ( Windeløv et al, 2017 ). However, consistent with active GLP-1 primarily being secreted in the postprandial state, previous studies in rodents and humans show that fasting plasma active GLP-1 levels do not change after bariatric surgery ( Cummings et al, 2010 ; Laferrère et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by using a C‐terminal assay, all molecular forms carrying the amidation would be detected, including any extended or degraded molecular forms (Windeløv et al. ). In addition, using the isolated perfused mouse intestine allowed us to determine any effect on secretion with much greater sensitivity compared to what would have been possible in in vivo studies in mice (Windeløv et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using the isolated perfused mouse intestine allowed us to determine any effect on secretion with much greater sensitivity compared to what would have been possible in in vivo studies in mice (Windeløv et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin sensitivity Hepatic glucose production Food intake and body weight [2,40] Natriuretic peptides (ANP, BNP)…”
Section: Positive Effectsmentioning
confidence: 99%
“…In fact, a study in pigs demonstrated that dual neprilysin and DPP-4 inhibition may have additive effects and therapeutic potential for type 2 diabetes, as combined neprilysin and DPP-4 inhibition was more effective at maintaining active GLP-1 levels and enhancing insulin secretion than inhibition of either alone [3]. Unlike DPP-4, which cleaves active GLP-1 at a single site to yield truncated GLP-1(9-36)amide, neprilysin degrades both active and truncated GLP-1 at multiple sites [2,40] (Fig. 2), limiting both GLP-1 receptor binding and activation.…”
Section: Considerations For Clinical Use Of Neprilysin Inhibitors In mentioning
confidence: 99%